Ado????o de c??digos de governan??a corporativa por organiza????es de um conglomerado financeiro brasileiro: an??lise dos motivos - Moura, Melquezedech de Lyra (2016)
Governance legislation is in place, but in recent years corporate governance best practice codes have been expanded to complement existing legislation and even to make corporate governance practices stricter than those currently in place. In Brazil, among the private institutions without any link with government regulatory or supervisory bodies, the Brazilian Institute of Corporate Governance (IBGC) has been outstanding in the task of elaborating and mainntaining a code of corporate governance. The objective of this study was to analyze the reasons for the adoption of the best corporate governance recommendations of this institute related to the Board of Directors. With the help of a questionnaire based on these recommendations, a survey was conducted to elucidate the reasons for their adoption. For the survey, 11 closed-end corporations from a group of 34 organizations belonging to a financial conglomerate in Brazil were selected.